Opioid-induced mitogen-activated protein kinase signaling in rat enteric neurons following chronic morphine treatment. - Celine Duraffourd (PLoS ONE, 2014)
Opioids, acting at μ opioid receptors, are commonly used for pain management. Chronic opioid treatment induces cellular adaptations, which trigger long-term side effects, including constipation mediated by enteric neurons. We tested the hypothesis that chronic opioid treatment induces alterations of μ opioid receptor signaling in enteric neurons, which are likely to serve as mechanisms underlying opioid-induced constipation. In cultured rat enteric neurons, either untreated (naïve) or exposed to morphine for 4 days (chronic), we compared the effect of morphine and DAMGO (D-Ala2,MePhe4,Gly-ol5 enkephalin) on μ opioid receptor internalization and downstream signaling by examining the activation of the mitogen-activated protein kinase/extracellular signal-regulated kinases 1 and 2 (MAPK/ERK) pathway, cAMP accumulation and transcription factor cAMP Response Element-Binding protein (CREB) expression. μ opioid receptor internalization and MAPK/ERK phosphorylation were induced by DAMGO, but not morphine in naïve neurons, and by both opioids in chronic neurons. MAPK/ERK activation was prevented by the receptor antagonist naloxone, by blocking receptor trafficking with hypertonic sucrose, dynamin inhibitor, or neuronal transfection with mutated dynamin, and by MAPK inhibitor. Morphine and DAMGO inhibited cAMP in naïve and chronic enteric neurons, and induced desensitization of cAMP signaling. Chronic morphine treatment suppressed desensitization of cAMP and MAPK signaling, increased CREB phosphorylation through a MAPK/ERK pathway and induced delays of gastrointestinal transit, which was prevented by MAPK/ERK blockade. This study showed that opioids induce endocytosis- and dynamin-dependent MAPK/ERK activation in enteric neurons and that chronic morphine treatment triggers changes at the receptor level and downstream signaling resulting in MAPK/ERK-dependent CREB activation. Blockade of this signaling pathway prevents the development of gastrointestinal motility impairment induced by chronic morphine treatment. These findings suggest that alterations in μ opioid receptor downstream signaling including MAPK/ERK pathway in enteric neurons chronically treated with morphine contribute to the development of opioid-induced constipation.